LECTURER PRACTICES ON CORRECTIVE FEEDBACK IN ENHANCING STUDENTS WRITING ACCURACY (A Descriptive Study to the 3rd Semester Students Of English Study Program At IKIP PGRI Pontianak) - Apriani, Vidia; Ikhsanudin, Ikhsanudin; Sada, Clarry (English Language Education Study Program, 2021)
Corrective Feedback has been the center of attention among language researchers and education experts. The purpose of this study is to find out the types of Corrective Feedback that the lecturer used to correcting the students writing errors. This study was designed in qualitative form. In this study, the participants were two English lecturers and the third-year semester students. These participants were interviewed about their preference of corrective feedback and how they applied corrective feedback in the teaching of writing in their class. In order to obtain the data, the researcher used interview and document analysis. To enrich the findings in this study, the researcher collected the answer sheets from 26 students in two interval periods. The results of the study revealed that grammar was the most corrected elements in writing, with the percentage of 49.25%, followed by vocabulary by 22.39% and organization and mechanic by 19.40% and 8.96%. These figures were consistent with the interview results where the lecturers stated that grammar is their focus for corrective feedback. This study also revealed that corrective feedback is something that the students expected from their lecturers.